A loss-of-function variant in OSBPL1A predisposes to low plasma HDL cholesterol levels and impaired cholesterol efflux capacity. (June 2016) - Motazacker, Mahdi M.; Pirhonen, Juho; van Capelleveen, Julian C.; Weber-Boyvat, Marion; Kuivenhoven, Jan Albert; Shah, Saundarya; Hovingh, G. Kees; Metso, Jari; Li, Shiqian; Ikonen, Elina; Jauhiainen, Matti; Dallinga-Thie, Geesje M.; et al.
Abstract: Background and aims: Among subjects with high-density-lipoprotein cholesterol (HDL-C) below the 1st percentile in the general population, we identified a heterozygous variant OSBPL1A p . C39X encoding a short truncated protein fragment that co-segregated with low plasma HDL-C. Methods: We investigated the composition and function of HDL from the carriers and non-carriers and studied the properties of the mutant protein in cultured hepatocytes. Results: Plasma HDL-C and apolipoprotein (apo) A-I were lower in carriers versus non-carriers, whereas the other analyzed plasma components or HDL parameters did not differ. Sera of the carriers displayed a reduced capacity to act as cholesterol efflux acceptors ( p  < 0.01), whereas the cholesterol acceptor capacity of their isolated HDL was normal. Fibroblasts from a p . C39X carrier showed reduced cholesterol efflux to lipid-free apoA-I but not to mature HDL particles, suggesting a specific defect in ABCA1-mediated efflux pathway. In hepatic cells, GFP-OSBPL1A partially co-localized in endosomes containing fluorescent apoA-I, suggesting that OSBPL1A may regulate the intracellular handling of apoA-I. The GFP-OSBPL1A-39X mutant protein remained in the cytosol and failed to interact with Rab7, which normally recruits OSBPL1A to late endosomes/lysosomes, suggesting that this mutation represents a loss-of-function. Conclusions: The present work represents the first characterization of a human OSBPL1A mutation. Our observations provide evidence that a familial loss-of-function mutation in OSBPL1A affects the first step of the reverse cholesterol transport process and associates with a low HDL-C phenotype. This suggests that rare mutations in OSBPL genes may contribute to dyslipidemias. Highlights: We found a heterozygous variant OSBPL1A p . C39X in subjects with high-density-lipoprotein cholesterol (HDL-C) <1st percentile. Sera of the carriers displayed a reduced capacity to act as acceptors for cholesterol efflux. Fibroblasts from a p . C39X carrier showed reduced cholesterol efflux to lipid-free apoA-I. GFP-OSBPL1A-39X protein remained cytosolic and failed to bind Rab7, the receptor of OSBPL1A on late endosomes/lysosomes. This is the first report on a human OSBPL1A mutation, and suggests that rare OSBPL mutations may contribute to dyslipidemias.